Man Bac: The Excavation of a Neolithic Site in Northern Vietnam - F. Oxenham, Marc; Matsumura, Hirofumi; Kim Dung, Nguyen (Terra Australis, 2011)
The site of Man Bac in the Red River Delta of Vietnam, one of the most meticulously excavated and carefully analysed of Southeast Asian archaeological sites in the past few years, is emerging as a key site in the region. This book carefully analyses the human and animal remains and puts them into context. The authors describe in detail the health status, the unusual demographic profile and the interestingly divergent affinities of the cemetery population, and discuss their meaning, particularly in association with evidence for the use of marine and terrestrial animal resources; they argue convincingly that the site documents a time when the face of the region's population was undergoing a fundamental shift, associated with a changing economic subsistence base. Physical anthropologists and archaeologists have argued for years over the timeline, the manner and the very nature of Southeast Asian population history, and this book is essential reading in this debate. Two supporting appendices describe the individual remains in detail.